Scheduling of batch process plant / Abdul Aziz Abu Bakar - Abu Bakar, Abdul Aziz (1995)
Batch production is used throughout the process industries for the manufacture of fine chemical, plastics, pharmaceuticals, paints, ceramics, cosmetics, or whatever production quantities are small, product value is very high or product demand pattern is changeable. This research work is devoted to software development of scheduling and control algorithm of batch process plant using shortest path method developed by Dijkstra and K* shortest path method developed by Jin Y. Yea These methods are selected due to the practicality and wide acceptance from the experts in the field. The software developed is menu-driven graphical tool for simulating schedules for studied model. By using Turbo Pascal programming language, major programs are linked and displayed. Basically this tool can successfully simulate the graphical presentation to solve the shortest path and K* shortest path problem.